Sequence analysis and structural modelling of major capsid protein L1 of avian papillomavirus from african Grey Parrot - Zacharia, Kadiayeno Egbunu; Yap, Yong Zi; Nurulhuda Najihah; Abdul Razak, Mariatulqabtiah (Malaysian Society for Molecular Biology and Biotechnology, 2024)
Papillomaviruses are non-enveloped, and icosahedral in structure with a double-stranded circular DNA. They are responsible for inducing regressing papillomas (warts) on mucosal or keratinized epithelia across a diverse range of species including mammals, reptiles, birds and fish. Unlike human and bovine papillomaviruses, avian papillomaviruses (AvPV) received little attention in terms of sequence analysis and protein structure repository. This may be due to the less severity of morbidity and mortality compared to papillomavirus disease manifestations in human. The African Grey Parrot (Psittacus erithacus) is the first avian species to have a complete AvPV genome sequenced (PePV). Nonetheless, sequence analysis of its genes is limited with no three-dimensional structure reported in Protein Data Bank. Therefore, the aims of this study are to analyse the sequence of major capsid protein L1 of PePV, to assess its physicochemical properties, to generate its secondary and three-dimensional structures and to elucidate the quality of the generated L1 structural models. The PePV L1 capsid protein was analysed using online bioinformatics tools namely NCBI GenBank, PaVE, MUSCLE, ProtParam, PSIPRED and SOPMA. SWISS-MODEL, RaptorX and C-I-TASSER were implemented for high-quality structural modelling prior to comparison using PyMOL and Molprobity. Results demonstrated that the PePV L1 capsid protein was slightly acidic and thermally-stable. Additionally, the PePV’s host specificity is closed related to Fringilla coelebs papillomavirus (FcPV1) and Serinus canaria papillomavirus (ScPV1), both of which infect birds from the Austravales clade. Structure predictions reveal slight structural difference and similarities albeit the SWIS-MODEL and C-I-TASSER showed relatively high-quality models which were considered as the basis for structural comparison and reliability. Further research on avian major capsid protein L1 of PePV is anticipated to improve the current knowledge on AvPV’s structure-function relationship thus control the viral transmission in endangered birds.